TANGGUNGJAWAB DAN AKIBAT HUKUM BAGI PEJABAT PEMBUAT AKTA TANAH TERKAIT PENYALAHGUNAAN BIAYA TITIPAN PEMBAYARAN PAJAK PERSEROAN TERBATAS DALAM JUAL BELI HAK ATAS TANAH - Shabrina Harahap; Felicitas Sri Marniati; Nur Hakim (Journal of Innovation Research and Knowledge, 2026)
The misuse of tax escrow funds by a Land Deed Official (PPAT) in transactions involving the transfer of land rights gives rise to legal issues, particularly when such funds belong to a limited liability company. This practice constitutes the use of funds for purposes other than those for which they were intended and results in financial losses to the limited liability company. The issues examined in this study concern the legal consequences faced by a PPAT who misuses escrow funds designated for the payment of taxes of a limited liability company in a land rights transfer transaction, as well as the legal liability of a PPAT who engages in such misuse of escrow funds. The theoretical framework employed in this research is Hans Kelsen’s Theory of Legal Responsibility and Soeroso’s Theory of Legal Consequences. The research method used is normative juridical research, namely legal research based on library materials or secondary data, consisting of primary, secondary, and tertiary legal materials. The research approaches employed include the statutory approach, case approach, analytical approach, and conceptual approach. The collection of legal materials is carried out by identifying and inventorying positive legal norms, book literature, journals, and other legal sources. The analysis of legal materials is conducted through legal interpretation, namely grammatical interpretation and systematic interpretation, as well as methods of legal construction, including analogical construction and legal refinement. The research findings indicate that the misappropriation of entrusted tax funds by a Land Deed Official (PPAT) gives rise to legal liability. In particular, civil liability arises from the contractual relationship between the Limited Liability Company and the PPAT in relation to the deposit of tax funds, as grounded in Article 1338 paragraph (1) of the Indonesian Civil Code. Accordingly, the PPAT’s misuse of such funds constitutes an unlawful act pursuant to Article 1365 of the Indonesian Civil Code, thereby obliging the PPAT to compensate the Limited Liability Company for its losses in accordance with Article 1243 of the Indonesian Civil Code.